2020
DOI: 10.1002/1348-9585.12159
|View full text |Cite
|
Sign up to set email alerts
|

Can self-monitoring mobile health apps reduce sedentary behavior? A randomized controlled trial

Abstract: Objective To examine whether the self‐monitoring interventions of a mobile health app reduce sedentary behavior in the short and long terms. Method We designed a double‐blind randomized control trial. Participants were selected from among the staff of a medical institution and registrants of an online research firm. Forty‐nine participants were randomly assigned to either a control group (n = 25) or an intervention group (n = 24). The control group was given only the la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 29 publications
(76 reference statements)
0
15
0
Order By: Relevance
“…Fifty‐six interventions used a single mHealth component: delivered wholly via an app (23/80, 28.7% 68–70,79,82,83,85,88,89,91,92,95–97,103,106–109,113,114,124,126,128–130 ), pedometer (not app based; 19/80, 23.8% 55,60–68,87,94,112,115,116,119,120,123,132 ), or text messages (14/80, 17.5% 51,72–75,84,90,93,96,110,111,117,118,125 ). The remaining 24 interventions used a combination of an app and text messages (7/80, 8.8% 59,99,101,104,122,127,131 ), wearable plus associated app (e.g., Fitbit app; 7/80, 8.8% 57,77,80,81,98,100,121 ), pedometer (not app based) along with text messages (4/80, 5.0% 54,71,86,133 ), or wearable and associated app and text messages together (3/80, 3.8% 76,78,105 ). Two studies (2.5%) used an app plus a pedometer (not an app‐based pedometer) 58,103 and one used a wearable plus associated and additional app (1/80, 1.3% 102 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Fifty‐six interventions used a single mHealth component: delivered wholly via an app (23/80, 28.7% 68–70,79,82,83,85,88,89,91,92,95–97,103,106–109,113,114,124,126,128–130 ), pedometer (not app based; 19/80, 23.8% 55,60–68,87,94,112,115,116,119,120,123,132 ), or text messages (14/80, 17.5% 51,72–75,84,90,93,96,110,111,117,118,125 ). The remaining 24 interventions used a combination of an app and text messages (7/80, 8.8% 59,99,101,104,122,127,131 ), wearable plus associated app (e.g., Fitbit app; 7/80, 8.8% 57,77,80,81,98,100,121 ), pedometer (not app based) along with text messages (4/80, 5.0% 54,71,86,133 ), or wearable and associated app and text messages together (3/80, 3.8% 76,78,105 ). Two studies (2.5%) used an app plus a pedometer (not an app‐based pedometer) 58,103 and one used a wearable plus associated and additional app (1/80, 1.3% 102 ).…”
Section: Resultsmentioning
confidence: 99%
“…There were 14 studies that did not report a specific physical activity‐related outcome measure (14/74, 18.9% 71,76,84,85,91,92,101,104,106–108,114,126,128 ). Of the six interventions that targeted sedentary behavior, two used a device (2/6, 33.3% 98,100 ), one used a questionnaire (1/6, 16.7% 109 ), one used both (1/6, 16.7% 59 ), and two did not report a specific outcome related to sedentary behavior (2/6, 33.3% 80,127 ). Of the seven interventions targeting sleep, four used a self‐reported measure (4/76 57.1% 77,109,111,114 ), two used a device (2/7, 28.6% 69,82 ), and one did not report a sleep‐related outcome measure (1/7, 14.3% 128 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent Japanese research demonstrated that without real-time feedback of individuals' current activity levels, subjective sedentary time might be underestimated compared with objective measurement of sedentary time. 53 Hence, it is expected that these possibilities would bias the results toward the null. Even though there was moderate heterogeneity throughout the study, our subgroup analysis of study characteristics identified some causes of this heterogeneity, such as publication year and study region.…”
Section: Discussionmentioning
confidence: 99%